1975
DOI: 10.1111/j.1365-2389.1975.tb01961.x
|View full text |Cite
|
Sign up to set email alerts
|

The Determination of Desorption Isotherms for Soil Phosphate Using Low Volumes of Solution and an Anion Exchange Resin

Abstract: Phosphate desorption isotherms were determined (a) by shaking I g soil with 3 ml O'OIM CaCl, solution plus different amounts of an anion exchange resin, and (b) by diluting soil with different volumes of O-OIM CaCl, solution. Adsorption isotherms were determined using a soil to solution ratio of I g to 3 ml. In soils of intermediate P status adsorption isotherms appeared continuous with desorption by method (a), but not with desorption by method (b), which predicted lower buffer powers than did (a). Method (a)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1976
1976
2002
2002

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 18 publications
2
12
0
Order By: Relevance
“…Desorption isotherms are developed using sequential extraction with a dilute salt solution (Bhatti[6], Okajima [22], Brewster [9], Fox [15]), dilution (Bhatti[6], Brewster [9]), or exchange resins (Raven[24], Bache [1], Brewster [9]). Resorption, or the sorption of P following sorption and desorption steps, has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Desorption isotherms are developed using sequential extraction with a dilute salt solution (Bhatti[6], Okajima [22], Brewster [9], Fox [15]), dilution (Bhatti[6], Brewster [9]), or exchange resins (Raven[24], Bache [1], Brewster [9]). Resorption, or the sorption of P following sorption and desorption steps, has rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…This parameter can vary with the volume of water present and the amount of exchanger used (Cooke and Hislop, 1963;Bache and Ireland, 1980). In one study (Brewster et al, 1975), the log of the water phase phosphate content (In Ps) was found to be linearly related to the total amount of P desorbed from the soil. In another investigation (Barrow and Shaw, 1977), the soluble P level (P 5 ) was found to be inversely proportional to the volume of solution and weight of exchanger used, and directly related to (Pr) 05 (where Pr was the amount taken up by the exchanger).…”
Section: Phosphate Distribution In Anion Exchanger/sediment Systemsmentioning
confidence: 99%
“…In another investigation (Barrow and Shaw, 1977), the soluble P level (P 5 ) was found to be inversely proportional to the volume of solution and weight of exchanger used, and directly related to (Pr) 05 (where Pr was the amount taken up by the exchanger). The amount of P desorbcd from soils can also be influenced by the amount of Ca 2 + in solution (Brewster et al, 1975;Barrow and Shaw, 1977).…”
Section: Phosphate Distribution In Anion Exchanger/sediment Systemsmentioning
confidence: 99%
See 2 more Smart Citations